Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 213850 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Ocyphaps lophotes (Temminck, 1822)" ] } The dataset includes 213850 records from 65 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003521-150316153013904/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences